HYPER-CORRUPTION THEORY (MICROECONOMIC ANALYSIS WITH THE USE OF GAME THEORY) - Valencik, Radim (European Scientific Journal, ESJ, 2014)
This paper discusses the corruption resistance (hyper-corruption). We use the exact models (in our case from the area of the game theory, the analysis of the game such as the Tragedy of the Commons) in decoding the social reality with regard to uncovering the phenomenon of structures based on mutual covering of violations of the generally accepted principles, its significance, description of its anatomy, evolution and operational mechanisms.